In slavery's wake making Black freedom in the world - Gardullo, Paul; Obenda, Johanna 1994-; Bogues, Anthony; Bunch, Lonnie 1952- (Smithsonian Books, 2024)
"The companion book to a groundbreaking exhibition on African American history and culture-with 150 powerful illustrations of people and objects."
"In association with the National Museum of African American History and Culture."
Keywords: Geschichte; Sklavenhandel; Abolitionismus; Sklaverei; Schwarze; Slavery / History; Transatlantic slave trade; Black people / History; Black people / Social conditions; Personnes noires / Histoire; Personnes noires / Conditions sociales; Rita Cox Black and Caribbean Heritage Collection